Water stored in cisterns of vulnerable communities in the region of Mato Grande/Rio Grande do Norte: Quality analysis and proposals for viable social technologies. (Research, Society and Development, 2022)
This article aims to assess the quality of water stored in cisterns, particularly in houses in the Mato Grande Region, an area in Rio Grande do Norte, Brazil, which has benefited from social government programs. Firstly, a survey was applied to the local population to collect information about the stored water (origin, uses, and treatment methods performed). Subsequently, water samples were collected to perform microbiological analyses. The results show that water is primarily used for many purposes, including drinking. Also, all samples were contaminated by Escherichia coli, a fecal coliform bacterium responsible for many diseases and health problems. These findings suggest the urgent need for public policies and investment in technologies, education, and social development to prevent the proliferation of pathogens in the reservoirs. In addition, the article discusses the most viable alternatives to ensure potable water consumption in disadvantaged populations: the development and large-scale implementation of low-cost intervention methodologies, for example, Social Technologies (TS), that are currently discussed in Brazil by different sectors. Through these actions, a plausible solution is being demonstrated to assist with social needs and, as a result, allow the effective reduction of the social exclusion of individuals in complete alignment with the different pillars of sustainable development established by the United Nations Organization (UN).